Manhaj Tarjih: Navigating Ijtihad in The Disruption Era - Fariadi, Ruslan; Ikasari, Aryani; Nafiza, Salwa (Universitas Muhammadiyah Surakarta, 2025)
The objective of this study is to examine how the era of disruption is accommodated within the framework of Muhamamdiyah's ijtihad fiqh and how this framework is designed to navigate a responsive fiqh in the era of disruption. A qualitative normative research approach was employed to collect data through relevant literature studies, which were then analyzed comprehensively using content analysis, in conjunction with the takhrij of fiqhiyah principles derived from the manhaj methodology of Muhamadiyah's ijtihad fiqh. The findings indicate that the methodology of ijtihad fiqh employed by Muhammaddiyah extracts core concepts from ushul fiqh principles and fiqh maxims, thereby identifying the underlying rationale behind the selection of these principles. Furthermore, this study explores how existing fiqh rulings of muhammadiyah reflect responses to the challenges of the era of disruption. The study's findings reveal that the era of disruption, functioning as an independent variable, exerts a significant influence on the design of Muhamamdiyah's ijtihad fiqh methodology, which is a dependent variable. This methodology is meticulously structured to produce fiqh that is not only responsive but also adaptive to the demands of the contemporary era. The novelty of this research lies in its correlational description between the era of disruption and Muhamamd's ijtihad fiqh methodology, demonstrating how this ijtihad method functions as a compass in addressing the dynamics of rapid change